FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN OBESITAS PADA ORANG DEWASA DI KOTA PADANG PANJANG - Nova, Maria; Yanti, Rahmita (Universitas Islam Negeri Walisongo Semarang, 2017)
Nowadays,estimated about 500 millions people (12%) of the population wolrldwide are obese. In Padang Panjang city, found obese category in adults 18 years and over as much as 37%, which is the highest prevalence compared with other districts or cities in West Sumatra. The purpose of this study was to assess factors related to obesity in adults in Padang Panjang. It is a cross sectional research. The population is the entire number of adults in Padang Panjang. The sample size is 178 people, taken by Simple Random Sampling. Data were collected by questionnaire and interview using Food Frequency Quantitative (FFQ). Data processing was done by SPSS and analyzed by Chi-square test at p value <0,05. The result showed that there were significant correlation between knowledge level (p =0,023), physical activity (p= 0,026), mean intake of energy (p=0,000)with obesity and no signiicant correlation between smoking habbits and obesity (p=0,344). We concluded that low physical activity and knowledge, as well as high energy intake were risk factors for obesity.Â